Kepemimpinan Berorientasi Pengetahuan dalam Peningkatan Kinerja Inovasi melalui Implementasi Manajemen Pengetahuan - Bima Hermastho (Universitas Wahid Hasyim Semarang, 2021)
Knowledge grows not only how knowledge can be diffused but how it can continue to generalize new synergies with effective management of intangible assets. Competition between companies makes companies use the knowledge they only have to make decisions in the process of generating new things. The role of knowledge-oriented leadership in organizational innovation is being the core of sustainable business growth, however knowledge-oriented leadership has failed to build a significant relationship between leadership and innovation. The results showed that Knowledge Oriented Leadership was proven to have a significant positive effect on Knowledge Diffusion and Knowledge Generation. Knowledge Oriented Leadership is not proven to have a significant positive effect on innovation performance. Knowledge Diffusion and Knowledge Generation have an effect proven to have a significant positive effect on innovation performance. Knowledge Diffusion and Knowledge Generation can mediate the relationship between Knowledge Oriented Leadership and Innovation performance.